Palmarès musicaux : où sont les femmes? - Vallet, Stéphanie (La Presse, 2019)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; culture populaire; discours dominant; discriminations; femmes* artistes; genre; inégalités; périodes historiques; québec; régions géographiques; systèmes d'oppressions; thématiques; travail

New methodology shows that 258 million children, adolescents and youth are out of school (UNESCO, 2019)
Three years after the adoption of Sustainable Development Goal 4 (SDG 4) and the promise to provide universal primary and secondary education, there has been no progress in reducing the global number of out-of-school children, adolescents and youth. This fact sheet by the UNESCO Institute for Statistics (UIS) highlights the most recent statistics on trends at the global and regional levels, based on a revised calculation method that provides more precise estimates of the out-of-school population.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; approches et analyses; discipline; femmes*; inégalités; périodes historiques; systèmes d'oppressions; éducation

Gouverner la vie privée: l'encadrement inégalitaire des séparations conjugales en France et au Québec - Biland, Émilie (Gouvernement en question(s), 2019)
"L'implication de l'État dans la vie privée pose problème : les individus ont davantage de droits que par le passé, mais certains de leurs comportements, jugés problématiques pour la collectivité, justifient un interventionnisme renouvelé, dans lequel acteurs privés et mécanismes de marché occupent une place croissante. En tension entre libéralisme et normalisation, cette action publique participe aux recompositions des rapports sociaux, entre les classes sociales, entre les genres, ainsi qu'entre la population majoritaire et les personnes racisées. Objet de vifs débats et de réformes récurrentes, la régulation par le droit des séparations conjugales est un observatoire précieux de ces recompositions, ici analysées à partir de trois enquêtes collectives, qualitatives et quantitatives, menées des deux côtés de l'Atlantique. En France comme au Québec, l'accès aux procédures, les interactions avec les professionnel.les et l'encadrement des modes de vie sont les trois dimensions constitutives du gouvernement de la vie privée. Cependant, chacun des contextes n'articule pas de la même manière inégalités de classe et inégalités de genre. En scrutant la production institutionnelle des inégalités privées, cet ouvrage invite à imaginer des voies alternatives, dans la sphère privée comme dans la sphère publique, pour que la politique des droits tienne ses promesses émancipatrices."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; droit des femmes*; droits des femmes*; europe; famille; france; hétérosexualité; inégalités; mariage; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; soc2262; soc2264; sociologie; systèmes d'oppressions; séparation; thématiques

Festivals de musique québécois : où sont les femmes ? - Croteau, Laurianne (Ici Radio-Canada, 2019)
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; discipline; femmes* artistes; inégalités; musique; méthodologie; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

La charge mentale, une source d’épuisement, - Lanteigne, Amélie (RQASF, 2019)
De nombreuses femmes se sentent surchargées mentalement, et avec raison. La charge mentale de plus en plus lourde que les femmes ressentent au quotidien est le fruit d’une accumulation de responsabilités multiples, qui dépasse largement le fait d’entretenir la maison et de s’occuper des enfants. Lorsque la charge mentale est trop grande, des problèmes psychologiques peuvent se manifester. Troubles anxieux, épuisement professionnel, dépression : l’épuisement au féminin est un phénomène de plus en plus répandu.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; charge mentale; conciliation famille-travail; famille; inégalités; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; travail

Neoliberal reform and family engagement in schools: An intersectional gender analysis - Nygreen, Kysa (Policy Futures in Education, 2019)
This article presents an exploration of the work of family engagement in a racially- and linguistically-diverse, high-poverty, urban school district in a state of continuous neoliberal reform. Drawing from qualitative research methods, it is argued that family engagement is being reshaped by the imperatives of educational neoliberalization while, at the same time, remaining out of touch with the needs and concerns of families who are racially stigmatized, linguistically diverse, and experiencing extreme economic insecurity. It is further argued that school personnel charged with family engagement carry out exploited, invisible, and emotional tasks that increase in quantity and intensity as the social safety net declines under neoliberalism. Applying an intersectional gender analysis of emotional labor and the re-privatization of social reproduction offers an illustration of how family engagement in neoliberal schools both exploits and reinforces hierarchies of race–class–gender while obscuring these processes through neoliberal discourses of individual responsibilization. © The Author(s) 2018.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; inégalités; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail émotionnel; états-unis

La petite histoire du travail invisible - L'R des centres de femmes du Québec (2019)
La petite histoire du travail invisible Voici notre vidéo sur les luttes féministes pour la reconnaissance du travail invisible! Elle est inaugurée en cette Journée nationale des centres de femmes du Québec #JNCF2019. Allez dans un centre près de vous pour continuer la lutte avec nous!Avec la participation L'R des centres de femmes du
Keywords: 1900-1999; 1960-1969; 2000 à aujourd'hui; 2010-2019; approches et analyses; discipline; foyer; groupes de femmes; histoire et politique; inégalités; justice sociale; militance; périodes historiques; ressource en ligne; sciences humaines; stage; systèmes d'oppressions; thématiques; travail; travail social

Delivered by women, led by men: A gender and equity analysis of the global health and social workforce - World Health Organization (Human Resources for Health Observer Series, 2019)
Demographic changes and rising health care demands are projected to drive the creation of 40 million new jobs by 2030 in the global health and social sector. In parallel, there is an estimated shortfall of 18 million health workers, primarily in low- and middle-income countries, required to achieve the Sustainable Development Goals (SDGs) and universal health coverage. The global mismatch between health worker supply and demand is both a cause for concern and a potential opportunity. Since women account for 70% of the health and social care workforce, gaps in health worker supply will not be closed without addressing the gender dynamics of the health and social workforce. The female health and social care workers who deliver the majority of care in all settings face barriers at work not faced by their male colleagues. This not only undermines their own well-being and livelihoods, it also constrains progress on gender equality and negatively impacts health systems and the delivery of quality care. In November 2017, the World Health Organization (WHO) established the Gender Equity Hub (GEH), co-chaired by WHO and Women in Global Health under the umbrella of the Global Health Workforce Network. The GEH brings together key stakeholders to strengthen gender-transformative policy guidance and implementation capacity for overcoming gender biases and inequalities in the global health and social workforce, in support of the implementation of the Global Strategy on Human Resources for Health: Workforce 2030, and the Working for Health five-year action plan (2017–2021) of WHO, the International Labour Organization (ILO) and the Organisation for Economic Co-operation and Development (OECD). In 2018, the GEH identified and reviewed over 170 studies in a literature review of gender and equity in the global health workforce, with a focus on four themes: occupational segregation; decent work free from bias, discrimination and harassment, including sexual harassment; gender pay gap; and gender parity in leadership. This report will inform the next phase of the work of the Global Health Workforce Network GEH, which seeks to use these research findings to advocate gender-transformative policy and action.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discours dominant; droits des femmes*; inégalités; inégalités salariales; projet charge mentale; périodes historiques; rapports sociaux de sexe; systèmes d'oppressions; thématiques; travail; travailleureuses de la santé